Enriching students' experience in logistics and transportation through simulation - Mohd Saifudin, Adam; Zainuddin, Nizamuddin; Bahaudin, Ahmad Yusni; Zalazilah, Mohd Hanizan; Jamaludin, Roslan (2015)
Student’s employability is crucial factor that brings development to all economy.The present study looked into simulation content development which is all about developing, enriching and the applications of internet protocols in order to enrich the workrelated competencies experience among graduate in the field of logistics and transportations.The study was carried out within multi-national and local manufacturing companies, third party companies and government agency which are selected from Peninsular Malaysia.The sampling of the study focuses on undergraduate studying technology management and logistics and transportation in the public universities.A framework was proposed in the study that will cover the education through simulation in logistics and transportation.A qualitative approach was mainly conducted to gather data in the study.The findings assert that the resources involved in the outbound and inbound processes are computerized documentation.The study contributes to the body of knowledge on the enrichment of the student’s employability.It also provided practical recommendation for the organizations, employees and fresh graduate from the universities.